Assessing Apoptosis Gene Expression Profiling with a PCR Array in the Hippocampus of Ts65Dn Mice. (5th May 2015) - Yu, Bin; Zhang, Bin; Zhou, Wen-bo; Wang, Qiu-wei; Yuan, Pei; Yang, Yu-qi; Kong, Jing
Abstract : It is well known that Down syndrome (DS) is a condition in which extra genetic material causes delays in the way a child develops, both mentally and physically. Intellectual disability is the foremost and most debilitating trait, which caused loss of cognitive abilities and the development of early onset Alzheimer's disease (AD). Ts65Dn mice were used in this study. We isolated the hippocampus. First, we used transmission scanning electron microscopy to directly observe the hippocampus and confirm if apoptosis had occurred. Second, we customized a PCR array with 53 genes, including several important genes related to cell apoptosis. Gene expression was detected by RT-PCR. There were varying degrees of changes characteristic of apoptosis in the hippocampus of Ts65Dn mice, which mainly included the following: nuclear membrane thinning, unevenly distributed chromosomes, the production of chromatin crescents, and pyknosis of the nuclei with some nuclear fragmentation. Meanwhile, three genes (API5, AIFM1, and NF κ B1) showed changes of expression in the hippocampus of Ts65Dn mice compared with normal mice. Only NF κ B1 expression was significantly increased, while the expressions of API5 and AIFM1 were notably decreased. The fold changes in the expression of API5, AIFM1, and NF κ B1 were 11.55, 5.94, and 3.11, respectively. However, some well-known genes related to cell apoptosis, such as the caspase family, Bcl-2, Bad, Bid, Fas, and TNF, did not show changes in expression levels. The genes we found which were differentially expressed in the hippocampus of Ts65Dn mice may be closely related to cell apoptosis. PCR array technology can assist in the screening and identification of genes involved in apoptosis.